SOSIALISASI MEMBANGUN KESADARAN INTERNET SEHAT DI KALANGAN ANAK DI PKBM HIKMAH - Firdaus, Ade Dian Febrian; Sasmita, Brigita Fauziastuti; Dwiyono, Dhoris Noverita Zambhia; Budiman, Muhammad Afriza; Hizrian, Muhammad Naupal; Nurhakim, Nazzal; Lumbantoruan, Ririn Indah; Khairunnisa, Rizka; Maulana, Robby Annand; Khaerun Nisa, Salwa (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The title of this socialisation activity is Building Healthy Internet Awareness among Children The rapid development of the internet is a challenge for children to use it wisely and safely. However, this ease of access also brings great challenges related to wise and safe use. The lack of understanding about digital literacy can lead to negative impacts, such as exposure to inappropriate content, cyberbullying, and internet addiction. This socialisation programme at PKBM Hikmah aims to build healthy internet awareness through digital literacy education, introduction to healthy concepts, and application of parental controls. The methods used include needs analysis, action plan development, and implementation of educational sessions. This activity includes interactive education sessions for children as well as assistance to parents and educators. The results of the programme showed a significant increase in the understanding of internet risks, how to maintain privacy, and how to activate time restrictions on the internet. The programme also provided practical guidance for parents and educators to assist children in using the internet wisely. In conclusion, the programme successfully achieved its objectives by providing the necessary knowledge to support positive development for children in the digital age.